Ragam Bahasa dalam Khutbah Jum’at - Hidayat, Dudung Rahmat; Munandar, Didih Syakir (TAJDID, 2017)
The khutbah has its own distinct language, different from other spoken languages. The result of the research shows that the varieties of the Khutbah language are colored by the language interference which is found in all linguistic elements, whether in phonology, morphology, diction, syntax or discourse. The dominant language interference is from Arabic. The phenomenon arises because of the function of the Khutbah itself, which cannot be separated from the ritual activities whose source, namely the Qur'an and hadith, is provided with Arabic. Another peculiarity is that the Khutbah is heavily colored by advice and solicitation. In addition, there are critical statements of Khatib on societal issues and religious life. Thus, it became the medium of introspection not only for the hearers, but also for Khatib himself.